2017
DOI: 10.1016/j.taap.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Genistein prevention of hyperglycemia and improvement of glucose tolerance in adult non-obese diabetic mice are associated with alterations of gut microbiome and immune homeostasis

Abstract: Although studies have linked soy phytoestrogen 4,7,4-trihydroxyisoflavone genistein (GEN) to reduced type 1 diabetes (T1D) risk, the mechanism of dietary GEN on T1D remains unknown. In our studies, adult non-obese diabetic (NOD) mouse model was employed to investigate the effects of GEN exposure on blood glucose level (BGL), glucose tolerance, gut microbiome, and immune responses. Adult male and female NOD mice were fed with either soy-based or casein-based diet, and received GEN at 20 mg/kg body weight by gav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 57 publications
4
46
0
Order By: Relevance
“…However, the interaction between the gut microbiome and phytoestrogens may not be unidirectional. Non-obese diabetic mice fed with the phytoestrogen genistein, have been shown to have significantly different gut microbial beta-diversity linked to immune homeostasis [7]. Gut microbiota alteration following phytoestrogen consumption may be a factor in the alleviation or causation of cancer.…”
Section: Cancer and Phytoestrogensmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the interaction between the gut microbiome and phytoestrogens may not be unidirectional. Non-obese diabetic mice fed with the phytoestrogen genistein, have been shown to have significantly different gut microbial beta-diversity linked to immune homeostasis [7]. Gut microbiota alteration following phytoestrogen consumption may be a factor in the alleviation or causation of cancer.…”
Section: Cancer and Phytoestrogensmentioning
confidence: 99%
“…Similarly, the host microenvironment of the gut influences the gut microbiome [6]. The gut microbiome has been shown to be influenced by estrogen, however, the gut microbiome also significantly impacts estrogen levels [7,8]. The gut microbiome impacts estrogen levels in the host through the secretion of β-glucuronidase, an enzyme which deconjugates estrogen, enabling it to bind to estrogen receptors and leading to its subsequent physiological downstream effects [9].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that therapeutic administration of phytoestrogens (genistein and daidzein) ameliorates EAE, which is correlated with a decrease in the production of proinflammatory cytokines and an increase in the production of anti-inflammatory cytokines [159][160][161][162][163][164]. Phytoestrogens are also protective in the nonobese diabetic mouse model of T1D [165] and were associated with shifts in the gut microbiome [166]. A recent study by Berer et al [27] demonstrated that mice transplanted with fecal samples from healthy human controls, which developed a lower frequency of spontaneous EAE than mice transplanted with MS fecal samples, harbored a higher abundance of Adlercreutzia then MS fecaltreated mice.…”
Section: Phytoestrogen Metabolismmentioning
confidence: 99%
“…Additionally, a range of herbal-derived products including berberine, resveratrol, alliin, capsaicin, betacyanins, and cranberry proanthocyanidins have bioactions and antidiabetic effects potentially mediated by modulation of gut microbiota. [60][61][62][63][64][65][66][67] Galactomannan, pectin, capsaicin, and red pitaya betacyanins altered the proportion of Firmicutes to Bacteroidetes. 62,65,66 Increased fecal butyrate concentration and Roseburia abundance and decreased Bacteroides and Parabacteroides abundances have been reported after intervention by capsaicin in obese diabetic ob/ob mice.…”
Section: Herbal Agents Used To Treat T2d and Gut Microbiotamentioning
confidence: 99%